Découverte d’une culture africaine et fantasmes d’un missionnaire. Le Dictionnaire français-kirundi du Père Van der Burgt (1903) entre ethnographie, exégèse biblique et orientalisme - Jean-Pierre Chrétien (Afriques)
One of the first exogenous looks on the Great Lakes region of Africa came from a missionary in Burundi, the Dutch White Father Van der Burgt. He published in 1903 a French‑Kirundi encyclopaedic dictionary, which left a lasting influence on that countries scholarship. This book was both based on fieldwork and poorly‑controlled ethnographic, historical and biblical scholarship. It expressed a peculiar racial obsession : the quest for the Oriental origins of African populations and particularly the inclusion of the Tutsi category into a Hamito‑Semitic stock. Van der Burgt was even influenced by esoteric forms of orientalism, which drove his thoughts as far as India, Polynesia, or the revelations of the German mystic Catherine Emmerich. The Burundese culture was thus trapped by this imagination born out of the European libraries and it was described as the result of degeneration, based on the myth of the curse of Ham.